Hubungan Pengasuhan Orangtua dengan Motivasi Berprestasi Siswa yang Berasal dari Keluarga Miskin di Kota Padang - Nila Rahmawati; Mudjiran Mudjiran; yusri yusri (Indonesian Institute for Counseling, Education and Therapy (IICET), 2017)
Achievement motivation can encourage students to learn. In achieving success requires the support of parents. Poverty makes some parents from poor families have little time to guide the children. Consequently, parenting is not going well. This research aims to describe the relationship of parenting and achievement motivation of students who come from poor families. This research is quantitative descriptive with correlation metod. The population in this study are all students of SMP Negeri which in category BSM receiver in Padang. Total sample of 170 students, selected by cluster random sampling technique. Data was collected using Likert scale model measurements. Analysis of data using statistical techniques of correlation with the data collected in interval form Then analyzed using percentages. Testing the hypothesis by using the Pearson product moment correlation. The findings of this study are: (1) parenting students who come from poor families in Padang are in good enough category. (2) achievement motivation of students who come from poor families in Padang in low category. (3) There are significant positive relationship between parenting and achievement motivation of students who come from poor families. This result meant that better the care of the parents, the higher achievement motivation of student. Counselor in cooperation with school personnel and parents to encourage students increase achievement motivation.